Removal of boron from aqueous solution using magnetic carbon nanotube improved with tartaric acid - Zohdi, Nima; Mahdavi, Fariba; Abdullah, Luqman Chuah; Choong, Thomas Shean Yaw (Tehran University of Medical Sciences (TUMS), 2014)
Boron removal capacity of multi-walled carbon nanotubes (MWCNTs) modified with tartaric acid was investigated in this study. Modification of MWCNTs with tartaric acid was confirmed by Boehm surface chemistry method and fourier transform infra-red (FT-IR) spectroscopy. Experiments were performed to determine the adsorption isotherm and adsorption thermodynamic parameters of boron adsorption on tartaric acid modified MWCNTs (TA-MWCNTs). The effect of variables including initial pH, dosage of adsorbent, contact time and temperature was investigated. Analysis of data showed that adsorption equilibrium could be better described by Freundlich isotherm and the maximum adsorption capacities obtained at the pH of 6.0 was 1.97 mg/g. The estimated thermodynamic values of free energy (ΔG°), entropy (ΔS°) and enthalpy (ΔH°) indicated a spontaneous and an endothermic process. Furthermore, the TA-MWCNTs was magnetized for separation of boron-contaminated adsorbent from aqueous solution by applying magnetic field. The results showed that magnetic TA-MWCNTs particles were separated effectively after adsorption from contaminated water.